2019
DOI: 10.1111/joa.12925
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal changes in myogenic protein expression by the microenvironment after freeze injury

Abstract: Skeletal muscle has the remarkable capability to regenerate itself following injury. Adult myogenic stem cells (MSCs) are responsible for the repair and regeneration, and their activity is controlled by intrinsic and extrinsic factors. The aim of this study was to examine and compare the expression levels of Pax3, Pax7, MRF and p38 proteins during the course of regeneration and in different areas of the focal freeze-lesion damaged adult rat TA muscle. Using the focal freeze injury model, immunohistochemistry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…Contusion injury in rat models often results in change to MyoD expression within 4 to 8 hours post-injury, which declines by 8 days [5]. In contrast, prior research with cryoinjury models has shown that MyoD and Myf5 initially downregulate for 7 days, after which PAX7 downregulation occurs, enabling SC proliferation through expression of the early MRFs [35]. This may explain why MyoD expression changes were analysed more often from 7 days onwards, and why a significant increase was noted by most of the studies analysing expression at this time.…”
Section: Myogenic Determination Factormentioning
confidence: 99%
See 3 more Smart Citations
“…Contusion injury in rat models often results in change to MyoD expression within 4 to 8 hours post-injury, which declines by 8 days [5]. In contrast, prior research with cryoinjury models has shown that MyoD and Myf5 initially downregulate for 7 days, after which PAX7 downregulation occurs, enabling SC proliferation through expression of the early MRFs [35]. This may explain why MyoD expression changes were analysed more often from 7 days onwards, and why a significant increase was noted by most of the studies analysing expression at this time.…”
Section: Myogenic Determination Factormentioning
confidence: 99%
“…Cryoinjury generally exhibits distinct and well-characterized layers of damage, which are known to result in different MRF expression and regulation depending on the extent of tissue damage and should be considered a factor when analysing MRF expression [35]. Given the early expression of MyoD in some cases of skeletal muscle injury, it is unexpected that only one study analysed the effect at day 1 [26].…”
Section: Myogenic Determination Factormentioning
confidence: 99%
See 2 more Smart Citations